Generation Z: Shaping modern day universities by rethinking student success - VA Hayman Barber (Academic Chairpersons Conference Proceedings, 2020)
Generation Z is fully emerged in higher education. This generation is shaking up traditional practices in higher education and looking for relationship building, digital platforms and an understanding of the value of education. This workshop will guide participants to explore ways to help Gen Z be successful in higher education.
Keywords: Student Engagement; Course Design; Issues; Generation Z; Student success